2500 years of anthropogenic and climatic landscape transformation in the Stymphalia polje, Greece. (1st June 2019) - Seguin, Joana; Bintliff, John L.; Grootes, Pieter M.; Bauersachs, Thorsten; Dörfler, Walter; Heymann, Christian; Manning, Sturt W.; Müller, Samuel; Nadeau, Marie-Josée; Nelle, Oliver; Steier, Peter; Weber, Jan; et al.
Abstract: Lacustrine sediments generally record landscape development in the lake's catchment area controlled by palaeoclimatic and human induced changes. To improve our understanding on the anthropogenic and climatic influences on landscape development in Southern Greece for the last 2500 years, we report a 2 m-long, continuous high-resolution sedimentary record from shallow Lake Stymphalia (Peloponnese, Greece). Our proxies record climatically as well as anthropogenically induced landscape changes, influencing the lake area and lake depth. The Classical-Hellenistic era reflects a moderate, stable Mediterranean climate with low sedimentation rates. The parallel existence of the highly populated, major ancient city of Stymphalos, on the contemporary lake edge, doesn't seem to have caused lasting alterations in the record. The construction of the Hadrianic Aqueduct in the Roman era, ca. 130 AD, however causes an influential transformation in the lake development. It has a lasting effect on the lake hydrology as well as the vulnerability of this ecosystem. During Late Roman times, 5th to 6th century cal AD, the abandonment of the aqueduct combined with cooler climate conditions allows lake levels to recover. A phase of very high climatic instability was identified for the subsequent Early Byzantine (EB) period, during the 7th and 8th century cal AD. For this period, the later phase of the Late Antique Little Ice Age (LALIA), our proxies indicate further cooling and highly fluctuating water availability in a rather small lake area. The Middle Byzantine (MB) Period (9 th -12th century AD) is characterized by an over fivefold increase in sedimentation rates. Since local population was still well below Classical levels, we explain this singular period through an interaction of modest increase in land use but marked by careless management of deforested areas, warm and wet climatic conditions during the Medieval Warm Period and long-term effects of vulnerability caused by the aqueduct construction. Probably during this phase, the lake level rose through unparalleled sedimentary infill to flood and bury a significant part of the Lower Town of the abandoned ancient city. The Late Byzantine Period (13th and 14th century AD) sees core evidence for erosion of established, non-vegetated soils (high magnetic susceptibility), in a period of almost total depopulation. In the subsequent Ottoman era (late 15th – early 19th centuries AD) local settlement made only slight recovery, the climatic conditions seem less stable during the Little Ice Age (LIA) and the lake seasonally and later periodically starts to dry up, cumulating in a longer dry phase at the end of the 19th century AD, when agricultural activity on the polje floor was possible. The conclusion conforms with recent modelling of environmental change, critical of mono-causation, rather focussing on complex interactions of human and natural factors in the inception of landscape transformation.